2011
DOI: 10.4081/es.2011.e16
|View full text |Cite
|
Sign up to set email alerts
|

A positive effect of intranasal insulin on spatial memory in rats with neonatal diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is associated with cognitive impairments. However, their causal factors and the approaches to be used in their treatment have not been fully clarified and further study is needed. The aim of this work was to study the effect of intranasal insulin (I-I) on cognitive functions in rats with experimental T2DM. Neonatal rats (5 days old) were treated with an intraperitoneal (i.p.) administration of a single dose of streptozotocin (STZ) (80 mg/kg i.p.) which in adult animals leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
1
4
0
1
Order By: Relevance
“…Compared with Diabetic group, the Diabetic+ Insulin and Diabetic+ Janumet groups exhibited a significant elevation in serum insulin levels in the current study. This result corroborated the preceding findings (18,23,24) . However, the Diabetic+ Janumet group exhibited a significant elevation in serum insulin levels compared with Diabetic+ Insulin group.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with Diabetic group, the Diabetic+ Insulin and Diabetic+ Janumet groups exhibited a significant elevation in serum insulin levels in the current study. This result corroborated the preceding findings (18,23,24) . However, the Diabetic+ Janumet group exhibited a significant elevation in serum insulin levels compared with Diabetic+ Insulin group.…”
Section: Discussionsupporting
confidence: 92%
“…As a support, Chistyakova et al . [ 34 ] owed the cognitive deficit in rats with neonatal T2DM to the reported low brain insulin concentration and impaired insulin receptor substrate-2-mediated signaling pathways in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the 135-day therapy with I-I prevents the decline of AC stimulation induced by PACAP-38 in the diabetic brain. us, the ability of I-I to restore AC signaling pathways regulated by PACAP-38 and some biogenic amines may be one of the main mechanisms of positive in�uence of I-I on the impaired CNS functions in human and experimental DM [16,24,32]. e AC effect of dopamine, contrary to the other investigated hormones, did not change in the diabetic brain.…”
Section: Column 1: Group Namementioning
confidence: 92%